Myotonia Congenita (Thomsen's Disease) Report of Five Cases in a Family - Hardiono D. Pusponegoro; Jahja Zacharia; Jimmy Passat (Paediatrica Indonesiana, 1991)
This report describes 5 out of 8 siblings who were the first cases of myotonia congenital diagnosed in our department. The parents were first cousins. Neither the parents, nor the other family members have myotonia. The affected siblings 4 boys and 1 girl, all showed a very typical myotonia especially after prolonged rest, and it could be worked off with, continuing activity. They had a muscular looking body or a herculean proportion. The diagnosis were based upon family history, clinical findings of percussion myotonia, had grip myotonia, prominent muscular hypertrophy and confirmed by electromyographic examination revealing myotonic discharges. Since there were some junctional impairments, these patients were treated with diphenylhydantoin and then with quinine sulphate, with good results. The patients related parents were much likely to be heterozygous for the same harmful recessive genes, because they had common ancestor. The role of marriage counseling is important in this kind of inherited disease, to prevent the occurrence of this inherited disorder in the next generations.